Opinion Mining From Text Based On Machine Learning Approach - Bechoua Abla - Halouadji Abir (university of eloued جامعة الوادي, 2024)
في هذا العمل، نصف محاولتنا لتقييم أداء أساليب التعلم الآلي في تحليل المشاعر والآراء المعبر عنها في البيانات النصية بإستخدام SemEval - 2017Task4 تحليل المشاعر في تويتر. لقد اخترنا subtaskA لتصنيف المشاعر على مستوى الرسالة، ولقد إستخدمنا خوارزميات تعلم الآلة الخاضعة للرقابة تقنيات تضمين الكلمات مثل Tf - Idf و Bow و Word2Vec .نقدم أيضًا طريقة معالجة مع نصية مناسبة لرسائل الشبكات الاجتماعية، والتي تقوم بالترميز وتحويل الكلمات و أكثر يمكن أن يكون هذا العمل مفيد للغاية للشركات والمؤسسات التي ترغب في فهم تعليقات العملاء أو تتبع سمعة العلامة التجارية أو تحليل التصور العام لموضوعات معينة. In this work we describe our attempt to evaluate the performance of machine learning methods in analyzing sentiment and opinions expressed in text data with SemEval-2017 Task 4 “Sentiment Analysis in Twitter”. We chose subtask A for Message-Level Sentiment Classifcation, We use supervised maching learning algrothims with word embeddings techniques such as Tf-Idf , Bow and Word2Vec. Also, we present a text processing method suitable for social network messages, which performs tokenization, word lemmatization and more. This work can be extremely valuable for businesses and organizations that want to understand customer feedback, track brand reputation, or analyze public perception of certain topic
memouer mastr informatuque
Keywords: استخراج اللآراء، تحليل المشاعر العواطف، معالجة اللغات الطبيعية .; Opinion Mining; Sentiment Analysis; Emotions; Natural Language Processing.